Is It the Same Every Summer for the Euphausiids of the Ross Sea? - Andrea De Felice; Ilaria Biagiotti; Giovanni Canduci; Ilaria Costantini; Sara Malavolti; Giordano Giuliani; Iole Leonori (Diversity, 2022)
The pelagic ecosystem in the Ross Sea has one central component that is very important for energy exchanges between upper and lower trophic levels: the Middle Trophic Level. Krill species are the most important and abundant organisms within this level. Several acoustic surveys were conducted in the western Ross Sea over the past 25 years, revealing that Euphausia superba is by far the most abundant species of krill in the Ross Sea during austral summer, and that its core distribution is concentrated in the northern part, bordering the Southern Ocean. Euphausia crsytallorophias, the second most abundant krill species, is more concentrated in the central Ross Sea, generally near the coast. Data on krill biomass were collected in December and January from 1994 to 2016 and analyzed together with key environmental parameters by means of two-way ANOVA in order to explain species behavior and identify possible environmental drivers. Temperature and dissolved oxygen influenced the biomass of both species of krill, while other environmental parameters only affected one species. In conclusion, the biomass of both species has varied over the years, possibly due to a complex synergy of environmental drivers.